2019
DOI: 10.1051/ject/201951026
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin Anticoagulation for an Infant with Hyperbilirubinemia and Elevated Plasma-Free Hemoglobin on ECMO

Abstract: Heparin has been used for decades as an anticoagulant in patients on mechanical circulatory support, which includes extracorporeal membrane oxygenation (ECMO) and ventricular assist devices. Bivalirudin is a direct thrombin inhibitor that can be used as an alternative anticoagulant in neonates and infants demonstrating inaccurate heparin monitoring. We report a case of a 2-month-old male child who was placed on ECMO for severe acute respiratory distress syndrome. His ECMO course was complicated by severe hemol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This last characteristic is particularly attractive to ECMO patients, as clots bound in the circuit can lead to further worsening of plasma-free hemoglobin release and its deleterious effects. 11 Our institutional experience showed a survival to hospital discharge rate of 67% in the bivalirudin group compared with 57% in the heparin group, with no increased risk of bleeding or thrombotic complications associated with the use of a DTI in pediatric patients supported with ECMO in a PCICU. There was a higher prevalence of neurologic events and deaths associated in the heparin group; however, this factor can also be associated to higher rates of ECPR in this group.…”
Section: Discussionmentioning
confidence: 77%
“…This last characteristic is particularly attractive to ECMO patients, as clots bound in the circuit can lead to further worsening of plasma-free hemoglobin release and its deleterious effects. 11 Our institutional experience showed a survival to hospital discharge rate of 67% in the bivalirudin group compared with 57% in the heparin group, with no increased risk of bleeding or thrombotic complications associated with the use of a DTI in pediatric patients supported with ECMO in a PCICU. There was a higher prevalence of neurologic events and deaths associated in the heparin group; however, this factor can also be associated to higher rates of ECPR in this group.…”
Section: Discussionmentioning
confidence: 77%
“…The final systematic review was comprised of 28 publications involving 329 patients. There were 14 case reports, 16 17 18 19 20 21 22 23 24 25 26 27 28 29 13 retrospective cohort studies, 30 31 32 33 34 35 36 37 38 39 40 41 42 and 1 prospective study 43 ( Table 2 ). All articles were published between 2002 and 2022 ( Supplementary Material S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 28 studies, 22 (totaling 135 patients) reported bleeding rates while receiving IV DTI on ECMO. 17 18 19 20 21 22 23 24 25 26 27 28 29 30 33 36 37 38 39 42 However, only one study 36 classified bleeding according to standard criteria of major or minor bleeding. 44 The overall weighted average rate of bleeding was 17% and was 8.9%, 33.3% and 0% for those receiving bivalirudin, argatroban, and lepirudin, respectively ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations